Research protocol to evaluate the effectiveness of shockwave therapy, photobiomodulation and physical therapy in the management of non-insertional Achilles tendinopathy in runners: a randomised control trial with elective cross-over design. Issue 3 (27th September 2022) - Tenforde, Adam S; Vogel, Katie E L; Tam, Joshua; Silbernagel, Karin Grävare
Abstract : Background: Achilles tendinopathy (AT) is a common overuse injury in runners. While the mainstay of treatment for AT is tendon loading exercises (physical therapy and exercise programme (EXER)), some patients have refractory symptoms. Extracorporeal shockwave therapy (ESWT) and photobiomodulation therapy (PBMT) have each been evaluated to facilitate tendon healing; the influence of combining treatments is unknown and limited studies have been completed in runners. This randomised control study, with an elective cross-over at 3 months, will evaluate the efficacy of three forms of treatment of non-insertional AT: (1) EXER (loading programme specific to Achilles tendon combined with physical therapy); (2) EXER and ESWT; (3) EXER, ESWT and PBMT. Sixty runners will be assigned using block randomisation into one of three treatment groups (n=20). After 3 months, each participant may elect a different treatment than previously assigned and will be followed for an additional 3 months. The EXER Achilles loading programme will be standardised using the Silbernagel at-home programme. The primary outcome of interest is treatment group responses using the Victorian Institute of Sports Assessment—Achilles (VISA-A) Score. Secondary outcomes include the Patient-Reported Outcomes Measurement Information System—29 questions, the University of Wisconsin Running Injury and Recovery Index, heel raise to fatigue test, hopping test and ultrasound measurements. We will also capture patient preference and satisfaction with treatment. We hypothesise that the cohorts assigned EXER+ESWT+PBMT and EXER+ESWT will see greater improvements in VISA-A than the EXER cohort, and the largest gains are anticipated in combining ESWT+PBMT. The elective cross-over phase will be an exploratory study and will inform us whether patient preference for treatment will impact the treatment response. Trial registration number: NCT04725513 .